Neonatal lupus erythematosus successfully treated by exchange transfusion: a case report and literature review - Zhou, Minqian; Sun, Wenqiang; Peng, Hanghang; Zhu, Xueping (Frontiers in Pediatrics, 2024)
Introduction There are few reports of severe hematological involvement in children with neonatal lupus erythematosus (NLE) treated with exchange transfusion. In this case report, we present a female patient with NLE admitted to the Children's Hospital of Soochow University. The main clinical manifestations were pancytopenia and congenital heart block (CHB). Her condition was serious and could not be improved by conventional treatment; however, she responded well to exchange transfusion therapy. Case presentation A female infant, aged 1 month and 3 days, was admitted to the Children's Hospital of Soochow University owing to the “discovery of thrombocytopenia over 1 month.” She tested positive for anti-SSA IgG, anti-Ro-52 IgG, and anti-mitochondrial M2 antibodies. In contrast, her mother tested positive for ANA (1:320) and anti-Ro/SSA antibodies. The patient was diagnosed with NLE and presented with pancytopenia and CHB. Her cardiac function was normal and no intervention was performed; however, her hematological involvement was more severe, without significant improvement after steroid, intravenous immunoglobulin, and transfusion treatments. After exchange transfusion therapy, the patient significantly improved, and the short-term follow-up prognosis was good. Conclusion For patients with NLE presenting with hematological involvement that cannot be improved by conventional treatment or whose condition is serious, exchange transfusion therapy should be considered to reduce antibody titers and improve their condition.